Investigating motivations for customers to use interactive self-service technology in fast-food restaurant - Samengon, Harnidah; Che Ishak, Farah Adibah; Ab Karim, Muhammad Shahrim; Ghazali, Hazrina; Arshad, Mohd Mursyid (Human Resource Management Academic Research Society, 2023)
Today's explosion of technology revolutionizes the fast-food industry worldwide, including Malaysia. Increasingly, restaurant management teams have begun to embrace technology to provide electronic services to customers without requiring direct interaction with personnel. These technological interfaces have known as self-service technologies (SSTs). However, the use of SSTs has been the topic of recent studies. The issues that arise include the customer's reluctance to use the SSTs caused by technical errors, device failure, and the customer's involuntary participation in self-service technology. Therefore, the indication of customer experiences to create a holistic understanding in implementing technological change for an individual is still lacking. Thus, this study aims to investigate why customers use SSTs in the fast-food industry? This study employs qualitative research using in-depth interviews with ten customers who have experienced using the SSTs and physical observation. Thematic analysis was used to analyse the interviews after verbatim transcription. Five motivations for customers' SSTs usage have been identified in this research: meeting needs, alternative options, convenience, access to lower prices and forced usage. As a result, restaurants may better serve customers by understanding the customer journey and using the research's findings to guide their service while providing SSTs.